Outcomes of Adult Liver Retransplantation: A Canadian National Database Analysis - Peter D. Yoon; Madhukar S. Patel; Carla F. Murillo Perez; Tommy Ivanics; Marco P.A.W. Claasen; Hala Muaddi; David Wallace; Bettina Hansen; Gonzalo Sapisochin (Canadian Journal of Gastroenterology and Hepatology)
Background. Liver retransplantation remains as the only treatment for graft failure. This investigation aims to assess the incidence, post‐transplant outcomes, and risk factors in liver retransplantation recipients in Canada. Materials and Methods. The Canadian Organ Replacement Register was used to obtain and analyse data on all adult liver retransplant recipients, matched donors, transplant-specific variables, and post‐transplant outcomes from January 2000 to December 2018. Results. 377 (6.5%) patients underwent liver retransplantation. Autoimmune liver disease and hepatitis C virus (HCV) were the most common underlying diagnoses. Graft failure was 7.9% and 12.5%, and overall survival was 77.1% and 65.6% at 1 year and 5 years, respectively. In contrast to recipients receiving their first graft transplant, the retransplantation group had a significantly higher incidence of graft failure p<0.001 and lower overall survival p<0.001. The graft failure and patient survival rates were comparable between second transplant and repeat retransplant recipients. Furthermore, there were no differences in graft failure and patient survival when stratified according to time to retransplantation. Recipient and donor age (HR = 1.12, p=0.011; HR = 1.09, p=0.008), recipient HCV status (HR = 1.81, p=0.014), and donor cytomegalovirus status (HR = 4.10, p=0.006) were predictors of patient mortality. Conclusion. This analysis of liver retransplantation demonstrates that this is a safe treatment for early and late graft failure. Furthermore, even in patients requiring more than two grafts, similar outcomes to initial retransplantation can be achieved with careful selection.